2012
DOI: 10.1590/s0365-05962012000600004
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 frequency in a group of patients with psoriatic arthritis

Abstract: BACKGROUNDHLA-B27 is associated with spondyloarthritis, a group of diseases that includes psoriatic arthritis. OBJECTIVESTo describe the HLA-B27 frequency in a group of Brazilian patients with psoriatic arthritis and correlate its presence or absence with their clinical manifestations. METHODSCross-sectional study with 44 psoriatic arthritis patients of a Rheumatology clinic. Demographic and social data were recorded, as were skin and joints clinical examination. HLA-B27 was tested. All data were processed des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The association with psoriasis could reflect a diagnostic bias as patients with psoriasis and HLA‐B27 have a higher chance of being diagnosed by the rheumatologist and of being identified in their axSpA database. However, it could also reflect a true clinical association as was suggested in previous studies …”
Section: Discussionmentioning
confidence: 57%
“…The association with psoriasis could reflect a diagnostic bias as patients with psoriasis and HLA‐B27 have a higher chance of being diagnosed by the rheumatologist and of being identified in their axSpA database. However, it could also reflect a true clinical association as was suggested in previous studies …”
Section: Discussionmentioning
confidence: 57%
“…However, the role of genetic factors seemed to be less strong in Asians [23,[26][27][28]. Positive family history of PsO was found in approximately 15% of our patients, probably due to less prevalent HLA-B27 or other genetic predispositions in Hong Kong and Asia [20,[26][27][28]. A recent Japanese trial by Tanaka et al highlighted an even smaller percentage (4%) of PsA cohorts with a family history of PsO [23].…”
Section: Discussionmentioning
confidence: 91%
“…The PSOLAR study of 12,000 skin psoriasis patients in North and Latin America found that 45.5% and 10.3% of them had a positive family history of PsO and PsA, respectively [25]. However, the role of genetic factors seemed to be less strong in Asians [23,[26][27][28]. Positive family history of PsO was found in approximately 15% of our patients, probably due to less prevalent HLA-B27 or other genetic predispositions in Hong Kong and Asia [20,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The high HLA-B27 positivity (90–95%) in AS patients suggests that HLA-B27 is strongly related to axial SpA. In contrast, the positivity is lower (22–36%) in PsA in which peripheral joints are mainly affected [ 11 , 12 ]. In addition, HLA-B27-positive PsA patients had a higher risk of axial involvement than did HLA-B27 negative PsA patients [ 13 ].…”
Section: Pathogenesismentioning
confidence: 99%